Adverse Outcomes and Potential Targets for Intervention in Gestational Diabetes and Obesity. Issue 2 (August 2015) - Scifres, Christina; Feghali, Maisa; Althouse, Andrew D.; Caritis, Steve; Catov, Janet
<x xml:space="preserve">Abstract</x> OBJECTIVE: To evaluate the association of obesity with pregnancy outcomes in women with gestational diabetes mellitus (GDM) and identify potentially modifiable risk factors for adverse outcomes in obese women with GDM. METHODS: This was a retrospective cohort study of 1, 344 women with GDM who delivered between 2009 and 2012. Demographic data, blood sugar values, gestational weight gain, and maternal and neonatal outcome data were abstracted from the medical record and compared among normal-weight, overweight, and obese women. RESULTS: Overweight and obese women had higher mean fasting and postprandial blood sugars despite higher doses of and more frequent use of medication. Obesity was independently associated with macrosomia (adjusted odds ratio [OR] 2.03, 95% confidence interval [CI] 1.07–3.89, P=.03), indicated preterm birth (adjusted OR 2.21, 95% CI 1.02–4.78, P=.04), and hypertensive disorders of pregnancy (adjusted OR 2.19, 95% CI 1.38–3.49, P=.001). In our stratified analyses, obese women with fasting blood sugars greater than 88.7 mg/dL and postprandial blood sugars greater than 123.8 mg/dL had higher rates of macrosomia (13.1% compared with 5.7%, P=.004 for fasting, 13.0% compared with 6.5%, P=.01 for postprandial blood sugars) and indicated preterm birth (11.4% compared with 6.1%, P=.04 for fasting, 11.9% compared with 5.8%, P=.01 for postprandial blood sugars) when compared with obese women with lower values. Hypertensive disorders of pregnancy were significantly increased in obese women with postdiagnosis weight gain greater than 0.6 lb per week (29.4% compared with 15.2%, P<.001) when compared with obese women with less weight gain. CONCLUSION: Prepregnancy obesity is independently associated with adverse pregnancy outcomes in women with GDM, and interventions to optimize glycemic control and limit weight gain postdiagnosis may improve outcomes in these high-risk women. LEVEL OF EVIDENCE: II